2017
DOI: 10.1293/tox.2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol extracts collected from the <i>Styela clava</i> tunic alleviate hepatic injury induced by carbon tetrachloride (CCl<sub>4</sub>) through inhibition of hepatic apoptosis, inflammation, and fibrosis

Abstract: The Styela clava tunic (SCT) is known as a good raw material for preparing anti-inflammatory compounds, wound healing films, guided bone regeneration, and food additives. To investigate whether ethanol extracts of the SCT (EtSCT) could protect against hepatic injury induced by carbon tetrachloride (CCl4) in ICR mice, alterations in serum biochemical indicators, histopathology, hepatic apoptosis, inflammation, and fibrosis were observed in ICR mice pretreated with EtSCT for 5 days before CCl4 injection. EtSCT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…For example, acetaminophen (paracetamol) is a common over the counter pain reliever, which may cause extensive hepatic trauma even after only a single over-exposure [ 27 ]. Environmental exposure to industrial toxins such as carbon tetrachloride (CCl4) has also been shown to cause vascular congestion and vacuolar degeneration [ 28 , 29 ]. Exposure of endogenous wildlife to a popular insecticide also caused observable hepatic damage in a similar way to that of CCl4 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, acetaminophen (paracetamol) is a common over the counter pain reliever, which may cause extensive hepatic trauma even after only a single over-exposure [ 27 ]. Environmental exposure to industrial toxins such as carbon tetrachloride (CCl4) has also been shown to cause vascular congestion and vacuolar degeneration [ 28 , 29 ]. Exposure of endogenous wildlife to a popular insecticide also caused observable hepatic damage in a similar way to that of CCl4 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The polysaccharides isolated from the tunic may have been responsible for the bioactivities previously observed in extracts of S. clava , such as UV protection [ 11 ], prevention of hepatic injury [ 12 ], and anti-inflammatory effects [ 13 ]. Further work would be required to test the biological activity of the individual polysaccharides found.…”
Section: Resultsmentioning
confidence: 99%
“…Besides nanocellulose, S. clava contains other valuable compounds responsible for a range of observed bioactivities. In mice, ethanolic extracts of S. clava tunics have been shown to protect the skin from UV radiation [ 11 ] and the liver from hepatic injury [ 12 ], and aqueous extracts have displayed anti-inflammatory effects [ 13 ]. Enzymatic hydrolysates from S. clava have produced anti-inflammatory effects in zebrafish [ 14 ], in vitro antioxidant activity and growth inhibition of several cancer cell lines [ 15 ], and antihypertensive effects in patients with type 2 diabetes and hypertension [ 16 ].…”
Section: Introductionmentioning
confidence: 99%